ECSE: A pseudo-SDLC game for software engineering class - Sakgasit Ramingwong (2018)
© 2018 by IGI Global. All rights reserved. Software development is uniquely different especially when compared to other engineering processes. The abstractness of software products has a major influence on the entire software development life cycle, which results in a number of uniquely important challenges. This chapter describes and discusses Engineering Construction for Software Engineers (ECSE), an effective workshop that helps software engineering students to understand some of these critical issues within a short period of time. In this workshop, the students are required to develop a pseudo-software product from scratch. They could learn about unique characteristics and risks of software development life cycle as well as other distinctive phenomenon through the activities. The workshop can still be easily followed by students who are not familiar with certain software development processes such as coding or testing.